Strategic Analysis of the Development of Agricultural Machinery and Equipment Service Business (UPJA) Barokah in Trimulyo Village, Jetis Subdistrict, Bantul Regency - Muhammad Razan Farras; Geraldo Adinugra Rimartin; R Hermawan (PAKIS JOURNAL INSTITUTE, 2026)
Agricultural Machinery Service Unit (Unit Pelayanan Jasa Alsintan, UPJA) Barokah is an agricultural economic institution that provides agricultural machinery and equipment services in Trimulyo Village, Jetis Kapanewon, Bantul Regency. UPJA plays an important role in supporting agricultural mechanization; however, its management still faces various internal and external constraints that affect business development. This study aimed to identify the internal and external factors influencing the performance of UPJA Barokah, formulate business development strategies using SWOT analysis, and determine priority strategies using the Quantitative Strategic Planning Matrix (QSPM) method. The study was conducted from November 2025 to April 2026 using a descriptive qualitative approach. Data were collected through interviews, participatory observation, Focus Group Discussion (FGD), and documentation. Data were analyzed using the IFAS, EFAS, SWOT, and QSPM matrices. The results showed that the total IFAS score was 2.29 and the EFAS score was 2.56, placing the organization in Quadrant III. This condition indicates that UPJA Barokah has considerable development opportunities but still faces internal weaknesses that need to be improved. Based on the SWOT matrix, the prioritized strategy was the Weakness–Opportunity (WO) strategy. The QSPM analysis showed that the main priority strategy was to increase member participation and regenerate operator human resources through role distribution and the introduction of agricultural mechanization to the younger generation, with a Total Attractiveness Score (TAS) of 6.09.